EXPANSION AND DIRECTION OF URBAN AREAS IN AL-DIWANIYAH CITY - Sawsan A AL-Omrani; Hamsa Zubaidi (Journal for Technology and Science, 2026)
Objective: Population growth and changes clearly impact any city's expansion and urban development, regardless of its natural and geographical characteristics. Despite the economic development and growth witnessed by Al-Diwaniyah after 2003, it suffers from many problems. Al-Diwaniyah experiences significant urban challenges, including traffic congestion, insufficient public services, the proliferation of informal settlements, and ongoing environmental degradation. The unregulated urban expansion has resulted in a significant increase in the built-up area over time, creating pressure on land use and existing infrastructure. Therefore, this study was conducted to determine the causes of these problems. Method: The use of Geographic Information Systems (GIS) was to explore the development in the urban areas to 2023, Results: the result shows that there is an expansion in the land used, as the area in 1958 was 1.5 03 km2, in 1972 the area reached 10.035 km2, while the area became 14.486 km2 in 2001, in 2008 the area became 17.4 38 km2. In 2014, the area increased to 26.1 111 km2, while the expansion of land use increased to 32.361 km2 in 2023, with expansion in the direction of the east of the city. This increase in land use is due to the population growth and economic growth in Iraq after the increase in oil revenues after 2003. Novelty: Among the most important reasons was that Diwaniyah is characterized by high population density and random expansion by encroaching on the lands adjacent to the city center.